Detection of stiffener disbonding in a stiffened aluminium panel using nonlinear Lamb wave. (March 2015) - Yelve, Nitesh P.; Mitra, Mira; Mujumdar, P.M.
Highlights: Higher harmonics induced in Lamb wave because of contact nonlinearity at the disbond are studied. Experiments are carried out on the disbonded stiffened panels using piezoelectric wafer actuators and sensors. The contact nonlinearity is modelled in the Finite Elements (FE) using the Augmented Lagrangian algorithm. Spectral Damage Index is estimated based on both the experimental and the FE results. Abstract: The present research focuses on detection and quantification of disbond present beneath the stiffener in a stiffened aluminium panel, using a Lamb wave based nonlinear technique. For this purpose, both experimental and finite element simulation studies are carried out. The contact nonlinearity at the disbond leads to the generation of higher harmonics in the Lamb wave response. This phenomenon is observed in both the experimental and the simulation studies. A Spectral Damage Index (SDI) defined by the authors is extracted from these higher harmonics. This SDI has a decreasing trend with the increase in the size of the breathing damage. The plots of the SDI against the disbond width observed in the cases of experimental and simulation studies are in the close agreement. Thus, the higher harmonics observed in the Lamb wave response and the SDI obtained from these higher harmonics together found to be effective in detection and quantification of the disbond in the stiffened aluminium panel.